Perancangan Aplikasi Pemesanan Bahan Makanan Frozen Toko Makmur Jaya - Candra, Claudio Erlisto; Hartanto, Michael Phrigyan; Alexander, Edwin (Jurnal Pengembangan Sistem Informasi dan Informatika, 2024)
In this digital era, online buying and selling transactions are increasingly popular with the public. This is also driven by increasing public awareness of the importance of convenience and efficiency in shopping. Toko Makmur Jaya, as a seller of frozen foodstuffs, has a great opportunity to develop in this digital era. By designing a special ordering application, Toko Makmur Jaya can reach customers more easily, increase sales and build customer loyalty. This research aims to design a frozen food ordering application for Toko Makmur Jaya that suits customer needs and desires. This research uses a qualitative research method with a case study approach. Research data was obtained through interviews with the owner of Toko Makmur Jaya and a survey of Toko Makmur Jaya customers. Based on the research results, the Toko Makmur Jaya frozen food ordering application needs to be equipped with features and functions which include: Complete and attractive product catalog, Easy to use and order, Various payments, Fast and reliable delivery, Attractive promotions and discounts Apart from these features and functions, the Toko Makmur Jaya frozen food ordering application also needs to be supported by an efficient and reliable logistics system to maintain the quality of frozen products. The success of the Toko Makmur Jaya application is not only determined by features and functions, but also several other important factors, such as branding and marketing, customer service, and continuous analysis and development..